Wiederbelebungsversuche. Mediologisches Erzählen in der deutschsprachigen Literatur der 1990er Jahre - Knorr, Carolin (KIT Scientific Publishing, 2018)
The narrations of many young authors of the 1990s operate under and in the terms of the new media at the same time, so the reader is able to observe how media change forms of communication. With the narration a well-known topic is repeated and reanimated. The presence of sensual effects of one medium in another is analysed by the mediological method, which also develops in the 1990s. So this way of narrating, which is significant for the 1990s, is called mediological narration.